Studyholism as a New Potential OCD-Related Disorder: What Evidence Have We Gathered until Now? A Narrative Review - Yura Loscalzo (Behavioral Sciences, 2024)
In 2017, Loscalzo and Giannini introduced the new potential clinical condition of studyholism (or obsession toward study) and a comprehensive model including its possible antecedents and outcomes. Then, emphasizing the value of avoiding an aprioristic (addiction) framework in analyzing problematic overstudying, they suggested conducting research on this new construct to unveil its internalizing and/or externalizing nature while also avoiding the over-pathologizing of a common behavior such as studying. Seven years after the first publication about studyholism, growing evidence concerning its antecedents suggested that studyholism might be defined as an OCD-related disorder (or, more generally, as an internalizing disorder). Moreover, the research about its outcomes highlighted that it is a problem behavior deserving attention as it is associated with academic, psychological, physical, and social downsides. Therefore, this paper aims to review the scientific literature published concerning studyholism to illuminate if it might be conceptualized as an OCD-related disorder based on its symptomatology, antecedents, and impact on individuals’ academic, physical, and psychological functioning. Given that it is a new construct, it is of critical value to systematize the findings gathered until now as it can help scholars interested in students’ well-being to have a clear understanding concerning the importance of screening studyholism since childhood, as this will help favor academic success and well-being and reduce the risk for school dropout. Finally, this paper presents an agenda for future research on studyholism, and it highlights the importance of further analyzing problematic overstudying using different theoretical perspectives (such as the behavioral addiction conceptualization) to unveil its real nature.